1970
DOI: 10.2466/pr0.1970.27.2.343
|View full text |Cite
|
Sign up to set email alerts
|

Level of Aspiration and Locus of Control in Disadvantaged Children

Abstract: Culturally disadvantaged and advantaged 6-yr.-olds were compared on level of aspiration and locus of control. There were no differences between disadvantaged Negro and white children on either measure, but disadvantaged children in general were characterized by higher and less accurate levels of aspiration with reference to specific performance tasks and by less internal locus of control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…One measure used in five of the studies is derived from the discrepancy between expectancy and actual performance, where expectancies are elicited either before (Fulkerson, Furr, & Brown, 1983;Milgram et al, 1970) or after performance (Boyd, 1952;Guggenheim, 1969;Stake, 1973). With either measure, large discrepancies would mean that individuals are either underestimating or overestimating the likelihood of future success in light of current performance.…”
Section: Expectancy For Successmentioning
confidence: 99%
“…One measure used in five of the studies is derived from the discrepancy between expectancy and actual performance, where expectancies are elicited either before (Fulkerson, Furr, & Brown, 1983;Milgram et al, 1970) or after performance (Boyd, 1952;Guggenheim, 1969;Stake, 1973). With either measure, large discrepancies would mean that individuals are either underestimating or overestimating the likelihood of future success in light of current performance.…”
Section: Expectancy For Successmentioning
confidence: 99%
“…Moreover, in school-related tasks, boys from a background of poverty typically are often observed to show much less persistance and much less ingenuity than do boys from middle-class backgrounds (J. Schickedanz, personal communication). Also, children from backgrounds of poverty show a substantially greater discrepanc between actual performance on test tasks and expressed levels of aspiration on these tasks than is found in children of the middle-class (Hieronymus, 1951;Keller, 1963;Milgram, Shore, Riedal, & Malasky, 1970). Class differences also appear on that dimension of personal style which Kagan (1965) has called "impulsivity-reflectivity."…”
Section: Recent Evidence Of the Nature Of The Educational Deficitmentioning
confidence: 99%
“…Other evidence generally supports the findings of Battle and Rotter (1963) and Gruen et al (1974) which indicated socioeconomic status rather than race contributed more substantially to locus of control differences. Milgram (1971), Milgram, Shore, Riedel, and Malasky (1970), and Stephens and Delys (1973b have all reported socioeconomic status rather than race accounted for locus of control differences in samples ranging from kindergarten to tenthgrade. In addition, locus of control has correlated with socioeconomic status in racially homogeneous samples (Gruen & Ottinger, 1969;Nowicki & Strickland, 1973).…”
Section: Clarification Of the Relationships Between Locus Of Control ...mentioning
confidence: 99%